2002
DOI: 10.1093/ageing/31.4.261
|View full text |Cite
|
Sign up to set email alerts
|

Dance-based aerobic exercise may improve indices of falling risk in older women

Abstract: dance-based aerobic exercise specifically designed for older women may improve selected components of balance and locomotion/agility, thereby attenuating risks of falling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
116
1
10

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(142 citation statements)
references
References 11 publications
15
116
1
10
Order By: Relevance
“…Short et al (2003) reported that aerobic exercise (45 min, 3 times per week for 16 weeks) was associated with improvements in muscle mass. Shigematsu et al (2002) reported that dance-based aerobic exercise (60 min, 3 times per week for 12 weeks) was effective at improving walking speed in older adults aged 65 years and over. These studies did not analyze results according to age subgroups, and did not report effects on mental health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Short et al (2003) reported that aerobic exercise (45 min, 3 times per week for 16 weeks) was associated with improvements in muscle mass. Shigematsu et al (2002) reported that dance-based aerobic exercise (60 min, 3 times per week for 12 weeks) was effective at improving walking speed in older adults aged 65 years and over. These studies did not analyze results according to age subgroups, and did not report effects on mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have shown that individuals aged 65 to 84 years can benefit significantly from aerobic exercise, improving physical function parameters such as muscle mass, balance, and walking speed (Shigematsu et al 2002;Short et al 2003;Harber et al 2009). In addition, a multicomponent exercise including aerobic exercise has been reported to have a positive impact on balance, gait speed, walking distance, and mobility in older adults aged 65 years and over (Eggenberger et al 2015) or aged 79 to 90 years (Rogers et al 2003;Ansai et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Pajala et al compared an ankle balance training group and an ankle muscle strengthening exercise group; the former showed less postural swaying than the latter. Shigematsu et al(2002) reported that when elderly persons were trained with single leg standing, squatting, marching, and heel touching, as well as targeted balance, strength, and locomotion/agility, three times per week for 12 weeks, the TUG time was shortened. Hwang Su-Jin reported that when elderly women performed ball exercises five times per week for eight weeks, the subjects' BBS scores improved statistically significantly compared to before the intervention.…”
Section: Resultsmentioning
confidence: 99%
“…The MMSE has been translated and validated into Portuguese by Bertolucci et al (13) The Timed Up and Go (TUG) test is widely used to assess the functional capacity of the elderly, as a predictor of falls. (14)(15)(16)(17) Its achievement is simple: consists in evaluating the normal speed at which a person rising from a chair with arms, walk three meters ahead, turns, walks back three meters and sits in the chair again. During this activity the time is timed.…”
Section: Diagnóstico E Estatístico Dos Transtornos Mentaismentioning
confidence: 99%